The use of Ground Penetrating Radar (GPR) in the definition of salt wedge penetration and groundwater monitoring in the estuarine Amazonian beach - Correia, Karolina Almeida (2019)
The association of survey data with records obtained through the use of the Ground Penetrating Radar (GPR), taking into account the climatic seasonality, in Praia do Farol (Mosqueiro Island / Belém-PA), revealed the behavior of the water table and the record of the penetration of the salt wedge into subsurface in this estuarine environment. The identification of the water table was very clear, revealing a transition between unsaturated zone and well-defined saturated zone. The GPR profiles show that the level of the top of the water table is registered as a strong horizontal reflector, diving towards the sea. The top of the water table in the post-beach zone is located approximately 1 meter deep in the rainy season (March), becoming deeper in the intertidal zone. During the dry season (November), the top of the surface of the sheet undergoes deepening, ranging from 1.9 meters in the supramarine zone to 2 meters in the intertidal zone. The soil moisture and, above all, the presence of salt in the beach sediments had a strong influence on the reflection signals, changing the dielectric constant of the sediments and, consequently, creating zones of signal attenuation, thus allowing mapping of the salt wedge in subsurface during the dry season. However, a geophysical study is recommended using other methods, seeking better results from a hydrogeological point of view.